Exit, Voice, and Political Change: Evidence from Swedish Mass Migration to the United States - Karadja, Mounir; Prawitz, Erik (Journal of Political Economy, 2019)
We study the political effects of mass emigration to the United States in the nineteenth century using data from Sweden. To instrument for total emigration over several decades, we exploit severe local frost shocks that sparked an initial wave of emigration, interacted with within-country travel costs. Our estimates show that emigration substantially increased the local demand for political change, as measured by labor movement membership, strike participation, and voting. Emigration also led to de facto political change, increasing welfare expenditures as well as the likelihood of adopting more inclusive political institutions.